2023
DOI: 10.1029/2023ja031327
|View full text |Cite
|
Sign up to set email alerts
|

Local Electron Density Depletions in the Martian Upper Ionosphere Obtained From MARSIS: Comparison With ASPERA‐3, and MAVEN, and the Connection With Crustal Magnetic Fields

F. Duru,
R. A. Frahm,
D. Hughes
et al.

Abstract: Steep electron density depletions in the Martian ionosphere are important, especially because they could be regions of significant plasma escape. Local electron density profiles of the Martian ionosphere obtained from the radar sounder onboard the Mars Express spacecraft often show large fluctuations. In some cases, these fluctuations are observed as deep depletions in the electron density. Investigation over the past 12 years of Mars Advanced Radar for Subsurface and Ionospheric Sounding data have revealed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…(2015), which were interpreted that precipitation of solar wind electrons is not an essential prerequisite for ionospheric structuring at Mars, and also with Duru et al. (2023), where suprathermal electron flux can either increase or decrease around plasma depletions in the Martian ionosphere. For completeness, the author has redrawn Figure 7 using only (a) dayside or (b) nightside SW electron data (the two figures not shown here), but the endeavor did not significantly improve the correlation between Martian ionospheric disturbances and SW electron density/temperature.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…(2015), which were interpreted that precipitation of solar wind electrons is not an essential prerequisite for ionospheric structuring at Mars, and also with Duru et al. (2023), where suprathermal electron flux can either increase or decrease around plasma depletions in the Martian ionosphere. For completeness, the author has redrawn Figure 7 using only (a) dayside or (b) nightside SW electron data (the two figures not shown here), but the endeavor did not significantly improve the correlation between Martian ionospheric disturbances and SW electron density/temperature.…”
Section: Discussionmentioning
confidence: 83%
“…Lately, Duru et al. (2023) analyzed in situ plasma density depletions encountered by MEX/MARSIS at altitudes between 276 and 1,111 km. They concluded that the plasma density depletions prefer crustal magnetic anomaly, but are not well correlated with co‐located suprathermal electron flux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation